Bimbingan Kepada Orang Tua, Tentang Penggunaan Gadged Bagi Anak Sekolah Minggu GKSI EFATA Sedawak - Sarah Sarah; Djulius Thomas Billo (Institut Nalanda, 2024)
In the current era of globalization, it is certainly very easy for us to search for information or communicate with one another using gadgets. Since the existence of gadgets, it is easier for us to interact even at long distances, both with relatives and friends. Almost all groups have it, both children and adults. However, the existence of gadgets nowadays has a bad impact, especially for children. The negative impact of using gadgets is that children tend to be individualistic, have difficulty socializing and if they are addicted, they will be very difficult to control, which in the end will make it difficult for the child's brain to develop because they play games too often. Therefore, the role of parents is very important in providing guidance in using gadgets to children. This research aims to understand and determine the impact of gadget use on children; understand the factors that support and hinder parents in dealing with children's behavior in using gadgets; and Knowing and understanding the role of parents towards children in using gadgets. The data analysis method used is a descriptive qualitative research method, namely conducting field research.